Father-son Attachment and Familial Dynamics: A Psychoanalytic Study of Bret Easton Ellis’s Lunar Park - Jan, Ameer; Mir, Shah; Jahangir, Saima (Regional Lens, 2025)
This study examines the application of Attachment Theory to Bret Easton Ellis’ novel Lunar Park (2005). It studies how early emotional connections in infancy with parental figures shape the protagonist’s emotional development, relational patterns, and sense of self. Using John Bowlby’s theoretical framework, which argues that early caregiver relationships form the foundation of later interpersonal relationship patterns, this study argues that Ellis is the product of emotionally distant parents, especially of his domineering father. The failure in emotional availability leaves psychological effects on his persona. Ellis fictionalises himself as Bret Easton Ellis, whose dominating and critical father generates a sense of inadequacy in him. This unhealthy paternal bond manifests in Ellis’ adult life as detachment, mistrust and emotional instability. These traits later impair his marriage and his relationship with his son. The novel thus reveals how inadequate paternal attachment perpetuates cycles of emotional malfunction across generations. By reading these texts through the lens of Attachment Theory, this study reveals that the protagonist’s emotional alienation is psychological prints formed within early familial settings. Ellis depicts the long-lasting consequences of insecure attachment that later affect his relationships in adulthood.